Increasing the cost of informal workers: Evidence from Mexico - Brenda Samaniego de la Parra; León Fernández Bujanda (Banco de México, 2020)
This paper estimates the effects of increasing the cost of informal jobs on formal firms' and workers' outcomes. We create novel datasets combining administrative records and household surveys data, and exploit exogenous variation in this cost generated by over 480,000 random work-site inspections in Mexico. Increasing the cost of informal jobs at formal firms leads to lower employment growth, lower formal job creation, and higher formal and informal job destruction. For informal workers, inspections increase the probability of being formalized at the inspected firm, but also increase the probability of dissolving the informal match. Transitioning to a formal job due to an inspection increases the probability of being poached to a new, formal job.
Keywords: D22; E26; J46; 330; Firm Behavior; Informal Economy; Informal Labor Market